2010
DOI: 10.1590/s0006-87052010000300026
|View full text |Cite
|
Sign up to set email alerts
|

Composição química e mobilização de reservas em sementes de soja de alto e baixo vigor

Abstract: RESUMOO estudo dos efeitos do vigor das sementes sobre os estádios iniciais do desenvolvimento das plântulas de soja é importante, já que compreendem o período de estabelecimento da cultura. Sementes de baixo vigor podem provocar reduções na velocidade de emergência e na produção de biomassa seca de plântulas, podendo afetar o estabelecimento da cultura. Este estudo teve por objetivo quantificar os componentes químicos e avaliar a capacidade de mobilização de reservas, na germinação de sementes de soja de alto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
1
24

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 14 publications
4
49
1
24
Order By: Relevance
“…According to Henning et al (2010) and Pereira et al (2015) more vigorous soybean seeds have higher soluble protein, starch and soluble sugars contents as well as higher reserves mobilization capacity http://dx.doi. org/10.1590/2317-1545v37n2148445 during germination, resulting in soybean seedlings with better initial performance.…”
Section: Introductionmentioning
confidence: 99%
“…According to Henning et al (2010) and Pereira et al (2015) more vigorous soybean seeds have higher soluble protein, starch and soluble sugars contents as well as higher reserves mobilization capacity http://dx.doi. org/10.1590/2317-1545v37n2148445 during germination, resulting in soybean seedlings with better initial performance.…”
Section: Introductionmentioning
confidence: 99%
“…O teor proteico geralmente está associado a sementes de melhor qualidade fi siológica, o que favorece o desenvolvimento inicial das plântulas, principalmente sob condições desfavoráveis (HENNING et al, 2010). Entretanto, a produção de sementes de elevado teor proteico pode estar associada à menor produtividade de sementes (kg ha -1 ) (LEMOS et al, 2004).…”
Section: Resultsunclassified
“…O maior teor de açúcares nas sementes pode ser vantajoso, devido ao fornecimento de energia para as sementes, o que resulta em sementes mais vigorosas (HENNING et al, 2010) e, consequentemente, em maior porcentagem de emergência de plântulas no campo.…”
Section: Ba -----------------Mg (G Kg -1 ) --------------------------unclassified
“…Some research has shown that the physiological quality of maize seed (Zea mays) is inluenced not only by environmental factors, but also by the genotype and its interactions with the environment Importance of amylases in seed quality (HOECKER et al, 2006;REIS et al, 2011;OLIVEIRA et al, 2013;. Many authors such as Rood et al (1990), Causse et al (1995), Gomes et al (2000), José et al (2004b), Hoecker et al (2006 and Reis et al (2011) relate quality to the inluence of heterosis or hybrid vigor in seed germination. In several of these studies, hybrid plants were found to have more eficient enzyme systems compared to other lineages.…”
Section: Developmentmentioning
confidence: 99%
“…It drives starch conversion into sugars used for embryo growth (HENNING et al, 2010). The α-amylases constitute an endoamylase family which catalyze the hydrolyzing the α-1.4 glycosidic linkages in starch, glycogen and other carbohydrates (FRANCO et al, 2002).…”
Section: A Lopes Et Almentioning
confidence: 99%